2020
DOI: 10.1093/ajcp/aqaa007
|View full text |Cite|
|
Sign up to set email alerts
|

Improved Recognition of Hematogones From Precursor B-Lymphoblastic Leukemia by a Single Tube Flow Cytometric Analysis

Abstract: Objectives To improve diagnostic accuracy in differentiating hematogones from leukemic blasts in cases of precursor B-lymphoblastic leukemia/lymphoma (B-ALL), particularly those that are posttreatment or after bone marrow transplant, and to provide an algorithmic approach to this diagnostic challenge. Methods A seven-color antibody panel including CD10, CD19, CD45, CD38, CD34, CD58, and CD81 was generated to assess the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…When evaluating normal B cell maturation, we confirmed a dim to positive expression of CD58 by early hematogones, with a gradual reduction of this level of expression during differentiation to the mature B cell stage, with a significant difference between hematogones I or II and B mature lymphocytes ( p = 0.0040 and p = 0.0009, respectively, Figure S4A), as previously observed (Chen et al, 2001; Don et al, 2020; Lee et al, 2005).…”
Section: Resultssupporting
confidence: 89%
“…When evaluating normal B cell maturation, we confirmed a dim to positive expression of CD58 by early hematogones, with a gradual reduction of this level of expression during differentiation to the mature B cell stage, with a significant difference between hematogones I or II and B mature lymphocytes ( p = 0.0040 and p = 0.0009, respectively, Figure S4A), as previously observed (Chen et al, 2001; Don et al, 2020; Lee et al, 2005).…”
Section: Resultssupporting
confidence: 89%
“…Approximately 75% of B-ALL cases express CD38, with a dimmer intensity than that expressed on HGs. The applicability of the underexpression of CD38 in B-ALL as a discriminating marker has been demonstrated in various studies examining its utility in MRD testing [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of CD22 allows gating of B cells in patients where CD19 may be lost or masked by targeted therapy (Cherian et al, 2018). CD58 is commonly used in other B‐ALL MRD panels (Coustan‐Smith et al, 2002; Keeney et al, 2018), and has been shown to be informative as an MRD marker (Shaver et al, 2015) and in differentiating haematogones from B‐ALL blasts (Don et al, 2020). Cost is also an important consideration for diagnostic laboratories, and the antibody panel we present is considerably less expensive than the EuroFlow panel.…”
Section: Discussionmentioning
confidence: 99%